Phylogeographic Assessment Reveals Geographic Sources of HIV-1 Dissemination Among Men Who Have Sex With Men in Kenya - Nduva, George M.; Otieno, Frederick; Kimani, Joshua; McKinnon, Lyle R.; Cholette, Francois; Sandstrom, Paul; Graham, Susan M.; Price, Matt A.; Smith, Adrian D.; Bailey, Robert C.; Hassan, Amin S.; Esbjörnsson, Joakim; et al. (Frontiers in Microbiology, 2022)
HIV-1 transmission dynamics involving men who have sex with men (MSM) in Africa are not well understood. We investigated the rates of HIV-1 transmission between MSM across three regions in Kenya: Coast, Nairobi and Nyanza. We analysed 372 HIV-1 partial pol sequences sampled during 2006-2019 from MSM in Coast (N=178, 47.9%), Nairobi (N=137, 36.8%), and Nyanza (N=57, 15.3%) provinces in Kenya. Maximum-Likelihood (ML) phylogenetics and Bayesian inference were used to determine HIV-1 clusters, evolutionary dynamics, and virus migration rates between geographic regions. HIV-1 sub-subtype A1 (72.0%) was most common followed by subtype D (11.0%), unique recombinant forms (8.9%), subtype C (5.9%), CRF 21A2D (0.8%), subtype G (0.8%), CRF 16A2D (0.3%), and subtype B (0.3%). Forty-six clusters (size range 2-20 sequences) were found – half (50.0%) of which had evidence of extensive HIV-1 mixing among different provinces. Data revealed an exponential increase in infections among MSM during the early-to-mid 2000s, and stable or decreasing transmission dynamics in recent years (2017-2019). Phylogeographic inference showed significant (Bayes Factor, BF>3) HIV-1 dissemination from Coast to Nairobi and Nyanza provinces, and from Nairobi to Nyanza province. Strengthening HIV-1 prevention programmes to MSM in geographic locations with higher HIV-1 prevalence among MSM (such as Coast and Nairobi) may reduce HIV-1 incidence among MSM in Kenya.